Verso una terminografia per il traduttore giuridico - Magris, Marella (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
It is often stated that the structure of a terminological data bank should be developed taking the user’s needs into account. Translation-oriented terminology is certainly no exception to this rule. The creator of a data bank for legal terminology should assess the specific problems typically found in legal translation as well as the use of terminological resources by legal translators. However , users’ needs and users’ behaviour are extensively investigated in specialised lexicography, but seem to be a rather under-researched area in terminology and termino graphy. By drawing on relevant lexicographic experience, some empirical observations on the terminological needs of LSP translators, and translationoriented terminography with particular reference to legal terminology, this study aims at developing a list of ‘questions’ (related to terminological problems), to which a legal translator should find answers in a properly constructed and reliable language resource.